LEISURE FACILITIES AND SOCIO-CULTURAL ANIMATION (Fiep Bulletin - online, 2014)
Society, in the last decades, has undergone great transformations, and these transformations have direct effects in the population's way of living. In an attempt to minimize these problems, public leisure policies have been developed in some Brazilian cities, and leisure facilities have been built. The objective of this study was to analyze the availability, geographical distribution an socio-cultural adherence to public parks (specific equipment) in the city of Campo Grande - MS. This research was characterized as an exploratory study, data concerning the availability or unavailability of leisure facilities and their distribution was collected through a non-structured interview with a representative from  Fundação Estadual de Esportes of Mato Grosso do Sul. To analyze Socio-cultural animation programs, public parks administrators were interviewed, but this time a structured pattern of interview was used. A form, especially developed to meet the needs of the study was used. It was verified that the city of Campo Grande has no problems concerning lack of leisure facilities, once it has five parks, three in the outskirts and two are centered. On the other hand, it was verified that socio-cultural animation has not been so successful, due to the fact there are activities directed to children in only two parks, and when it comes to the handicapped, there are activities in only one park. Despite the fact that the city has an effective policy regarding the spatial availability, an efficient socio-cultural animation program towards children and the handicapped lacks.
Keywords: Leisure; Public parks; Socio-cultural animation